Non-genetic factor and genetic parameter analysis for growth traits in Sumba Ongole (SO) cattle - Putra, W.P.B.; Agung, P.P.; Said, S. (Diponegoro University, 2018)
The aim of this study was to evaluate non-genetic factors and genetic parameters of the growth traits in Sumba Ongole (SO) cattle. The growth traits were consisted of birth weight (BW), weaning weight (WW), yearling weight (YW), average daily gain of pre-weaning (ADG1) and post-weaning (ADG2). Data from 143 heads of SO cattle (year 2011 to 2016) which raised at PT KAR were used in this study. Generalized Linear Model (GLM) analysis was performed to evaluate non-genetic effect including sex, year of birth, generation and season. Therefore, to evaluate genetic parameters, the heritability (h2) and genetic correlation (rg ) were performed using Paternal Halfshib Correlation method. The results showed that sex of calf had no significant effect (P>0.05) on BW, WW and YW, but year of birth had significant effect on those traits. The factor of season had significant effect on WW. The estimation of h2 values of growth traits were included high category (h2>0.30) and accurate (h2>SE) on BW (0.66±0.42), WW (0.65±0.44), YW (0.67±0.42), ADG1 (0.68±0.45) and ADG2 (0.70±0.43). The estimation of rg values were included high category (rg>0.50) and accurate (rg>SE) on BW-WW (0.87±0.63); BW-YW (0.95±0.87); ADG1-WW (0.99±0.34); WW-YW (0.98±0.48) and ADG1-YW (0.95±0.51). It was concluded that trait of WW could be used as selection criteria to increase YW trait in SO cattle.